Stabilization of bis(chlorogermyliumylidene)s within bifunctional PNNP ligand frameworks and their reactivity studies - Sahoo, Padmini; Raut, Ravindra K.; Maurya, Devesh; Kumar, Vikas; Rani, Pooja; Gonnade, Rajesh G.; Majumdar, Moumita (Dalton Transactions, 2019)
The diiminodiphosphine (L-im) and diaminodiphosphines (l-NH and l-NMe) with a bifunctional PNNP ligand framework have been employed to host two [GeCl](+) units leading to the formation of bis(chlorogermyliumylidene) 1-3, respectively. The synthetic route involves a 1:2 stoichiometric reaction between the PNNP ligand and GeCl(2)dioxane and the subsequent addition of two equivalents of chloride abstracting agent. Compound 1 is unstable towards coordinating solvents and Lewis bases, resulting in the displacement of the GeCl unit and the formation of rearranged products 4 and 5. However, the diaminodiphosphine coordinated Ge(ii) bis(monocation)s 2 and 3 proved to be stable and revealed their electrophilic behaviour towards the Lewis bases studied.